2022
DOI: 10.1002/epi4.12596
|View full text |Cite
|
Sign up to set email alerts
|

Scalp HFO rates are higher for larger lesions

Abstract: High‐frequency oscillations (HFO) in scalp EEG are a new and promising noninvasive epilepsy biomarker, providing added prognostic value, particularly in pediatric lesional epilepsy. However, it is unclear if lesion characteristics, such as lesion volume, depth, type, and localization, impact scalp HFO rates. We analyzed scalp EEG from 13 children and adolescents with focal epilepsy associated with focal cortical dysplasia (FCD), low‐grade tumors, or hippocampal sclerosis. We applied a validated automated detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
(103 reference statements)
2
13
0
Order By: Relevance
“…46 Indeed, non-invasive recordings of HFOs from the scalp suggested that scalp-recorded HFOs are greater for larger areas of damaged tissue. 47 In the present study, we found more HFOs in Tg2576 mice which have the most plaque pathology. 19 Notably, differences in HFO occurrence between models were robust in SWS but not during wakefulness or REM, which is interesting because SWS is the sleep stage when amyloid-β is being cleared from the brain.…”
Section: Potential Role Of Hfos In Monitoring Disease Progression In Adsupporting
confidence: 61%
See 1 more Smart Citation
“…46 Indeed, non-invasive recordings of HFOs from the scalp suggested that scalp-recorded HFOs are greater for larger areas of damaged tissue. 47 In the present study, we found more HFOs in Tg2576 mice which have the most plaque pathology. 19 Notably, differences in HFO occurrence between models were robust in SWS but not during wakefulness or REM, which is interesting because SWS is the sleep stage when amyloid-β is being cleared from the brain.…”
Section: Potential Role Of Hfos In Monitoring Disease Progression In Adsupporting
confidence: 61%
“…47 Indeed, non-invasive recordings of HFOs from the scalp suggested that scalp-recorded HFOs are greater for larger areas of damaged tissue. 48 Notably, we did not find a statistically significant correlation between the total number of HFOs and age of transgenic mice (Pearson r=-0.23, p=0.37, n=16; Supplemental figure 1A). Instead, we found a non-linear relationship between the total number of HFOs and age of transgenic mice (Supplemental figure 1B).…”
Section: Potential Role Of Hfos In Monitoring Disease Progression In Admentioning
confidence: 63%
“…47 Indeed, noninvasive recordings of HFOs from the scalp suggested that scalp-recorded HFOs are greater for larger areas of damaged tissue. 48 Notably we did not find a statistically significant linear correlation between the total number of HFOs and age of transgenic mice (Pearson r = −0.23, p = .37, n = 16; Figure S1A,B).…”
Section: Potential Role Of Hfos In Monitoring Disease Progression In Admentioning
confidence: 73%
“…Nevertheless, the delineation of the EZ using HFO (Frauscher et al, 2017;Thomschewski et al, 2019) has proven to be highly predictive of seizure outcome (Fedele et al, 2017b,c,d;Boran et al, 2019b;Chen et al, 2021;Dimakopoulos et al, 2021) and therefore, may improve the outcome of epilepsy surgery. Moreover, an accumulation of recent evidence suggests that HFO are also measurable by non-invasive scalp EEG (Andrade-Valenca et al, 2011;Boran et al, 2019c;Kuhnke et al, 2019;van Klink et al, 2019;Cserpan et al, 2021aCserpan et al, , 2022aTamilia et al, 2021;Noorlag et al, 2022). Therefore HFO are investigated as potential biomarkers to delineate the EZ but also to monitor disease severity and treatment response (Fan et al, 2020;Jacobs and Zijlmans, 2020).…”
Section: High Frequency Oscillations As a New Biomarker For Epileptog...mentioning
confidence: 99%